POLITICAL COMMUNICATION STRATEGY FOR WINNING THE PRABOWO-GIBRAN PAIR IN WEST JAVA IN THE 2024 ELECTIONS - Diah Fatma Sjoraida; Aat Ruchiat Nugraha; Bucky Wibawa Karya Guna (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
This study explores the political communication strategies used by the Prabowo-Gibran pair in the 2024 elections in West Java. By using a holistic approach that combines traditional and digital methods, the pair managed to reach various segments of voters. Audience segmentation is key in delivering campaign messages that are relevant and attractive to each demographic group. The quick response to current issues strengthens the couple's image as leaders who are responsive and care about the interests of society. In addition, collaboration with local media helps them to ensure balanced and positive coverage of their campaigns, as well as expand the reach of communication with the public. This study highlights the importance of holistic, responsive and collaborative political communication strategies in winning voter support in West Java.